Correlation between luminescence and structural evolution of colloidal silicon nanocrystals synthesized under different laser fluences. (11th December 2017) - Wu, W S; Hao, H L; Zhang, Y X; Li, J; Wang, J J; Shen, W Z
Abstract: We present a detailed investigation of the structural evolution and photoluminescence (PL) properties of colloidal silicon (Si) nanocrystals (NCs) synthesized through femtosecond laser ablation at different laser fluences. It is shown that the mean size of colloidal Si NCs increases from ∼0.97–2.37 nm when increasing laser fluence from 1.0–2.5 mJ cm −2 . On the basis of structural characterization, temperature-dependent PL, time-resolved PL, and PL excitation spectra, we identify that the size-dependent spectral shift of violet emission is attributed to the quantum confinement effect. The localized excitons' radiative recombination via the oxygen-related surface states on the surface of the colloidal Si NCs is employed to explain the origin of the blue emission.